Optional English Preperatory Programs after HEC 2016 Regulation: Opinions of Administrators on the Current Situation and Problems - Sedat Beceren; Ceyhun Yükselir; Ömer Faruk İpek; Gökhan Öztürk; Nalan Kızıltan; Belgin Aydın (Anadolu Üniversitesi Eğitim Fakültesi dergisi)
This study examines the current situation and the problems of optional foreign language preperatory programs after the regulation of Higher Education Council (HEC) on foreign language teaching in higher education institutions published in 2016. The participants were determined based on purposive sampling and they included 5 academic staff who had administrative positions at the Schools of Foreign Languages of five different state universities in Turkey. The data were collected through face-to-face semi-structured interviews and analysed based on a qualitative content analysis scheme. The findings revealed that the problems experienced in optional foreign language preperatory programs are categorized under three headings; low level of learner motivation, administration of the programs and the problems of the instructors. It was found that the students in these programs lost their motivation very early and did not meet the responsibilities required by the programs. In addition to this, the current regulations of these programs created certain administrative problems especially regarding the planning at the beginning of the year. It was also revealed that the instructors in these programs were exhausted because of the student profile and most of them suffered from serious burnout levels. Parallel with these problems, several suggestions were made in the conclusion for the betterment of optional foreign language prep programs.